Analysis of clinical risk factors of premature infants in Chinese women based on anemia status - Ou, Weiwei; Xu, Zhu; Liu, Dan (Frontiers in Pediatrics, 2025)
BackgroundAnemia in premature infants, a high-risk category of patients, has been shown to impose significant economic and psychological burdens on families and society at large. Anemia is the most prevalent disease among pregnant women. The impact of anemia on the clinical high-risk status of premature infants remains elucidated; therefore, this study aims to investigate the risk factor of clinical high-risk infants in Chinese women based on anemia status.MethodA retrospective analysis of the data from premature infants in four medical centres was conducted from January 2023–May 2025. The data, including demographic information, medical histories, gestational diseases, fetal development, and fetal position, were collected. The analysis to identify the factors contributing to the clinical high risk of premature infants was conducted between the anemia groups.ResultsA total of 191 subjects were involved, with an average age of 29.20 ± 5.00 years, but only 34 (17.8%) cases were classified as clinical high-risk. The mean weight of the infants was recorded as 2483 ± 458 g, and the mean gestational age was determined to be 34.96 ± 1.20 weeks, including 72(37.7%) females. A statistically significant variation was observed among the anemia groups concerning maternal age, hypertension, uterine abnormalities, scarred uterus, and placental abnormalities (p < 0.05). However, no statistically significant difference was found between high-risk and low-risk premature infants (p = 0.838). In the nonanemia group, a statistically significant difference was observed among the variables of gender, gestational hypertension, placental abnormalities, placental abruption, umbilical cord abnormalities, and fetal dysplasia (p < 0.05), with male was the protective factor [OR = 0.240, 95% CI = (0.076, 0.764)], while placental abruption [OR = 31.499, 95% CI = (2.707, 366.599)], and fetal dysplasia [OR = 16.927, 95% CI = (3.161, 90.630)] were risk factor. In the anemia group, mild anemia, severe anemia, and placenta previa were found to be statistically significant (p < 0.05), but only severe anemia was a high-risk factor [OR = 18.600, 95% CI = (1.757, 196.927)].ConclusionThe findings of this study demonstrate that anemia exerts a significantly different influence on the clinical high-risk symptoms of premature infants. These differences can provide important reference points for managing pregnant women.